Optimalisasi Jumlah Tenaga Kerja Melalui Pengukuran Waktu Kerja di CV ABP Mandiri - Christian Wisnu Ardana; Handy Febri Satoto (Jurnal Teknik Industri Terintegrasi (JUTIN), 2026)
CV. ABP Mandiri is an entity that focuses on manufacturing motorcycle components with a production method that is highly dependent on human labor. Continuous and repetitive activities and significant physical demands result in an increased workload for employees, so that the company's production targets cannot be achieved optimally. The study aims to find the ideal number of workers by using workload analysis. This study was conducted in the production department with 13 workers as research subjects. Data collection was carried out through direct observation, measuring work time using a stopwatch 30 times, and collecting data on production and effective working hours. The data obtained will be examined through an evaluation of data feasibility, calculating normal time, as well as predetermined time, and analyzing labor requirements using the workload analysis method. The findings of this study indicate that there are several work procedures that show a high level of workload, so it is necessary to adjust the number of workers to increase effectiveness, efficiency, and productivity in the production process.